Green synthesis of zinc oxide nanoparticles using ethyl acetate fraction of white frangipani leaves (Plumeria alba L.) and its application as antidandruff shampoo - Dian Riana Ningsih, Putri Caroline, Purwati Purwati, Zusfahair Zusfahair, Anung Riapanitra (Journal of Applied Pharmaceutical Science, 2025)
Dandruff and seborrheic dermatitis are scalp conditions caused by the body’s natural microorganisms. Shampoo serves as an alternative solution by removing impurities and inhibiting microbial growth. The ethyl acetate fraction of white frangipani leaves (Plumeria alba L.) exhibits antibacterial properties due to its secondary metabolite compounds. Zinc oxide nanoparticles (ZnO-NPs) possess antibacterial activity and are safe for use on human skin. This study aims to develop an antidandruff shampoo formulation by incorporating ZnO-NPs synthesized with ethyl acetate fraction. Processes involved include the extraction and fractionation, synthesis and characterization of ZnO-NPs, formulation and characterization of ZnO-NPs shampoo, and antibacterial activity test against Staphylococcus aureus. Ethanol extract yield was 15.14%, n-hexane fraction was 15.11%, ethyl acetate fraction was 8.83%, and the ethanol fraction was 53.77%. The antibacterial activity test showed that the ethyl acetate fraction exhibited the highest inhibition diameter at 1.81 ± 0.42 mm. Phytochemical tests revealed that the fraction contains polyphenols, flavonoids, saponins, alkaloids, and terpenoids. ZnO-NPs with optimal antibacterial activity were obtained using 0.15-M P. alba ZnO-NPs, which were then formulated and characterized into a nanoparticle shampoo. Based on the study, 0.15-M P. alba ZnO-NPs shampoo formulation effectively inhibited bacterial growth and demonstrated stability in the shampoo formulation.
Keywords: Ethyl acetate, P. alba L., S. aureus, Shampoo, ZnO-NPs